2020
DOI: 10.1038/s41598-020-71326-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous targeting of mitochondria and monocytes enhances neuroprotection against ischemia–reperfusion injury

Abstract: Ischemia-reperfusion injury impairs the efficacy of reperfusion therapy after ischemic stroke. cyclophilin D (cypD)-mediated openings of mitochondrial permeability transition pore (mptp) and subsequent monocyte-mediated inflammation are considered as major mechanisms of reperfusion injury. However, no medical therapies are currently available. Therefore, we have tested a hypothesis that simultaneous targeting of mPTP and inflammation confers substantial neuroprotection after cerebral ischemia-reperfusion. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…This result appears to differ from other previous findings [ 57 ] but is consistent with our previous report [ 11 ]. Okahara et al reported that both the mPTP opening and inflammation are necessary to improve the neurological outcomes after cerebral ischemia-reperfusion injury on experiments using cyclophilin D and CC chemokine receptor 2-knockout mice [ 60 ]. Hawrysh et al reported the mechanism of tolerance against anoxia in turtle neurons, finding that anoxia activates mito-K ATP channels, leading to matrix depolarization and triggering the transient opening of the mPTP and Ca 2+ release via the mPTP, and ultimately silencing the NMDARs in turtle neurons [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result appears to differ from other previous findings [ 57 ] but is consistent with our previous report [ 11 ]. Okahara et al reported that both the mPTP opening and inflammation are necessary to improve the neurological outcomes after cerebral ischemia-reperfusion injury on experiments using cyclophilin D and CC chemokine receptor 2-knockout mice [ 60 ]. Hawrysh et al reported the mechanism of tolerance against anoxia in turtle neurons, finding that anoxia activates mito-K ATP channels, leading to matrix depolarization and triggering the transient opening of the mPTP and Ca 2+ release via the mPTP, and ultimately silencing the NMDARs in turtle neurons [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial-targeted therapy of the nervous system gradually started from fundamental study to clinical application. Several novel therapeutic agents, such as cyclosporine A, Nicorandilan, and Mitochondrial calcium uniporter (MUC) by adjust the mitochondrion channel, reducing oxidative stress and Ca2+ overload, inhibiting ROS burst, protect nerve cells [34,35]. Further researches on these mitochondrial-targeted drugs might provide an available strategy for future POD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same line, in another work, PLGA-based polymeric NPs containing CsA (CsA-NPs) and pitavastatin (Pitava-NPs) were simultaneously administered to target mitochondrial dysfunction and monocyte-mediated inflammation in a mouse model of acute cerebral IR [ 47 ]. Through blocking MPTP opening and chemokine receptor-2-dependent inflammation, concomitant administration of CsA-NPs and Pitava-NPs at the time of reperfusion decreased infarct size and attenuated neurological deficits as compared to single administration of CsA-NPs or Pitava-NPs ( Figure 5 ).…”
Section: Simultaneous Drug Delivery For a More Efficient Combinatimentioning
confidence: 99%
“…Through blocking MPTP opening and chemokine receptor-2-dependent inflammation, concomitant administration of CsA-NPs and Pitava-NPs at the time of reperfusion decreased infarct size and attenuated neurological deficits as compared to single administration of CsA-NPs or Pitava-NPs ( Figure 5 ). Given the crucial involvement of MPTP opening and inflammation in promoting cardiac injuries, it is conceivable that a similar NP-based combination therapy could also provide benefits in CVD [ 47 ]. Finally, the highly versatile Mito-porter DDS can potentially be employed to achieve mitochondria-targeted multiple delivery of protective agents, including nutraceutics and CsA, for a more efficient combination therapy in CVD ( Figure 5 ).…”
Section: Simultaneous Drug Delivery For a More Efficient Combinatimentioning
confidence: 99%